Education–Occupation Mismatch and Its Wage Penalties in Informal Employment in Thailand - Tanthaka Vivatsurakit; Jessica Vechbanyongratana (Asian Development Review, 2021)
This study examines the incidence of vertical mismatch among formal and informal workers in Thailand. Using the 2011, 2013, and 2015 Thailand Household Socio-economic Surveys, the study analyzes the relationship between vertical mismatch and wage penalties and premiums across four types of workers: formal government, formal private firm, informal private firm, and informal own-account workers. The incidence of overeducation is modest among the oldest cohort (8.7%) but prevalent among the youngest cohort (29.3%). Government employees face the highest overeducation wage penalties (28.2%) compared to matched workers, while in private firms, informal workers have consistently higher overeducation wage penalties than formal workers. Educated young workers are increasingly absorbed into low-skill informal work in private firms and face large overeducation wage penalties. The inability of many young workers to capitalize on their educational investments in Thailand's formal labor market is a concern for future education and employment policy development in Thailand.